Escherichia coli RelA Regulation via Its C-Terminal Domain - Kaspy, Ilana; Glaser, Gad (Frontiers in Microbiology, 2020)
One of the most important stress responses in bacteria is the stringent response. The main player in this response is the signal molecule (p)ppGpp, which is synthesized by a Rel family protein. In E. coli, RelA is the main synthetase of (p)ppGpp in response to amino acid starvation. Although the synthetic activity of RelA is well understood, its regulation, is not yet fully characterized. The C-terminus domain (CTD) of the E. coli RelA is responsible for the regulation of the protein and for its complete dependency on wild type ribosome. The CTD contains three Cysteine residues, positioned in a very conserved order. Together with our previous results, we show in vitro the negative dominant effect of a part of the WT CTD (AA 564-744) named YG4 on RelA synthetic activity. This effect is abolished using mutated YG4 (YG4-638). In vitro and MS-MS analysis of the native RelA and the mutated RelA in Cys-638 (Rel638) in the presence of the native and mutated YG4 (YG4-638) reveals that RelA forms a homodimer via its CTD by the formation of a disulfide bond between the two Cys-638 residues. This supports our previous data which showed, using a two-hybrid system, interactions between RelA proteins via the CTD. Finally, we show in vitro that excess of the native YG4 inhibited RelA synthetic activity but did not affect the amount of RelA bound to the ribosome. Our results suggest that the regulatory mechanism of RelA is by the dimerization of the protein via disulfide bonds in the CTD. Upon amino-acid starvation, the dimer changes its conformation, thus activating the stringent response in the cell.